Thermal effect of femtosecond laser polystyrene processing. (September 2019) - Wang, Bing; Wang, XinCai; Zheng, HongYu; Lam, Yee Cheong
Highlights: Substrate temperature could increase significantly during fs laser-PS interaction. Large temperature increase at high laser intensity (high nonlinear absorption). At low laser intensity, large % of energy into heat in agreement with simulation. Plasma and ablation consumed significant amount of energy at high laser intensity. Abstract: The thermal effects during femtosecond laser polymer processing have been investigated. The temperature increase during the process was directly observed by employing an infrared camera. Our results showed that the temperature can increase significantly during the laser-material interaction process. This indicates that a large percentage of laser energy can be converted to heat energy and dissipated into the bulk material. The temperature change as a function of the laser intensity was investigated. Nonlinear absorption was observed and proved to be the major absorption mechanism during the femtosecond laser polymer interaction process. The simulated results of thermal effect with a 3D FE model were compared with the experimentally measured temperature profile. The mechanism involved in the laser beam-material interaction was discussed.